Effectiveness of Moringa Tempeh Burgers in Increasing Hemoglobin of Anemic Adolescent Girls - Laksmi Wardhani, Tri Martya Ningrum; Retno Dewi, Yulia Lanti; Febrinasari, Ratih Puspita (Media Gizi Indonesia, 2024)
Adolescent girls can avoid anemia by maintaining stable hemoglobin levels and consuming foods rich in nutrients and high in iron. Food sources with high iron content that can increase hemoglobin levels include Tempeh and Moringa. Tempeh and Moringa are notable sources of iron. Tempeh provides nutrients such as Fe, vitamin B12, and folic acid, while Moringa leaves contain 28.66 g of protein, 929.29 mg of calcium, 715.22 mg of phosphorus, 9.99 g of iron, and 2.32 mg of zinc per 100 g. This study investigated the effect of Moringa tempeh burgers on hemoglobin levels in anemic teenage girls. Using a quasi-experimental design, 51 anemic girls aged 13-15 were divided into three groups: a control group (K) given tempeh burgers without Moringa, treatment group 1 (P1) given tempeh burgers with 3g of Moringa leaf flour, and treatment group 2 (P2) given tempeh burgers with 12g of Moringa leaf flour. Each group included 17 participants who consumed the assigned burgers for 30 days. Results showed the average hemoglobin level changes before and after the intervention were 0.46 g/dl in K, 0.70 g/dl in P1, and 2.23 g/dl in P2. Statistical tests confirmed significant differences in hemoglobin levels pre- and post-treatment across all groups. The study concluded that Moringa tempeh burgers, particularly those with the highest amount of Moringa leaf flour, were most effective in increasing hemoglobin levels in anemic adolescent girls.